2018
DOI: 10.1001/jamadermatol.2018.2306
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Course and Treatment Outcome for Patients With Early Disseminated or Early Localized Lyme Borreliosis

Abstract: IMPORTANCE Multiple erythema migrans (MEM) has been suggested as a risk factor for unfavorable antibiotic treatment outcome compared with solitary erythema migrans (EM). However, no direct comparison of early Lyme borreliosis manifested as MEM with solitary EM has been undertaken. OBJECTIVE To investigate the potential differences in clinical course and treatment outcome between MEM and solitary EM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 25 publications
6
29
0
4
Order By: Relevance
“…Our study has shown that the majority of basic clinical and epidemiologic characteristics of EM before treatment with antibiotics were analogous in the two groups of women and consonant with previous findings in Slovenian patients with EM [35][36][37][38][39][40][41][42] and that the outcome after antibiotic treatment was excellent regardless of pregnancy. No subsequent objective manifestations of LB were established in either of the two groups, and the proportion of patients with symptoms at follow-up visits was even lower than found in other recent studies from Slovenia [37][38][39][40][41][42], possibly because only young, previously healthy patients were included in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study has shown that the majority of basic clinical and epidemiologic characteristics of EM before treatment with antibiotics were analogous in the two groups of women and consonant with previous findings in Slovenian patients with EM [35][36][37][38][39][40][41][42] and that the outcome after antibiotic treatment was excellent regardless of pregnancy. No subsequent objective manifestations of LB were established in either of the two groups, and the proportion of patients with symptoms at follow-up visits was even lower than found in other recent studies from Slovenia [37][38][39][40][41][42], possibly because only young, previously healthy patients were included in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…We do not have a reliable explanation for the observation that the pregnant women less often had ring-like EM despite similar duration of the skin lesion before treatment, but we stress that the findings in our control group are in agreement with previous reports in Slovenian patients with EM [35][36][37][38][39][40][41][42]. Furthermore, the proportion of reported constitutional symptoms accompanying EM was lower in the pregnant women, indicating that the course of EM during pregnancy was milder than in the age-matched non-pregnant women (Table 1, Figure 1), as also shown in previous reports on EM from the same region [35][36][37][38][39][40][41][42]. Our results indicate that the probability of reporting constitutional symptoms systematically decreases with gestation week at diagnosis of EM (EM was diagnosed a median 7 days after the appearance of the skin lesion) and that women infected during the later stages of pregnancy report fewer constitutional symptoms compared with those infected during the early phases of pregnancy, who are more similar to non-pregnant women.…”
Section: Discussionsupporting
confidence: 82%
“…The 1220 patients included in this study were ≥18 years of age with EM defined according to European criteria [8], and were enrolled prospectively in five clinical trials between June 2006 and October 2015 at the Lyme borreliosis outpatient clinic, University Medical Center Ljubljana, Slovenia [2,4,9,10,11]. Patients were referred by their general practitioners, and only exceptionally by other specialists.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple EM is defined as the presence of two or more erythemas, at least one of which must fulfil the size criterion for solitary EM [12]. Patients with multiple EM were over-represented in our sample because they were enrolled preferentially in two of the clinical trials in the present analysis [10,11]; patients with previous LB were under-represented because such patients were excluded from two of the eligible trials [2,9]. Patients were categorized as young (18–44 years), middle-aged (45–64 years), or elderly (≥65 years) [13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation